54.1k views
3 votes
Can anyone help with this one quick

Can anyone help with this one quick-example-1
User Nsane
by
4.6k points

1 Answer

4 votes

Answer:

I'm assuming that they want you to expand these terms. Does that sound familiar?

You'll notice that the middle step is very helpful. They have exanded it for you and are giving you free headway.

y and z are both factored out to give us a free y and z for the square root expression on the end. All the rest are left in their end form.

So, therefore

x exponent=a=12

y exponent=b=8

z exponent=c=4

Have a great day!!

User Ibrahima
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.